PENGARUH FAKTOR FISIOLOGI, PERHATIAN, MINAT, PEMENUHAN KEBUTUHAN, PENGALAMAN, DAN SUASANA HATI TERHADAP KUALITAS LAYANAN - Siti Juriyah; Yulianto Yulianto; Noverman Duadji (Center of Language and Cultural Studies, 2019)
The objective to be achieved through this research is to determine the factors that affect the quality of service for students of the Faculty of Medicine (FK), University of Lampung (Unila), both partially and simultaneously. This type of research is correlational research. The population of this study was 771 students in FK Unila, and the number of sample was set at 91 students. The data were collected using instruments that have been developed by researchers. Valid and reliable data were analyzed using the latest version of the SPSS software program. The output of this study concludes that there are significant effects between physiological factors, attention, interest, experience, and mood on the quality of services available at FK Unila, both partially and simultaneously.